Influence of remote earth and impulse polarity on earthing systems by field measurement - Abdullah, S; Nor, NM; Agbor, N; Reffin, M; Marinah Othman (Inst Engineering Technology-Iet, 2024)
Indexed by WOS/SCOPUS/ERA